Kesiapsiagaan Masyarakat Dalam Menghadapi Bencana Banjir Di Kelurahan Kadipiro Kecamatan Banjarsari Kota Surakarta Tahun Ajaran 2015/2016 - Indariani, Rita, Drs. Yuli Priyana, M.Si (2016)
This research aimed at knowing: (1) the level of risk of flood disaster in Kadipiro Urban Village, (2) the level of raediness of the society regarding the flood disaster in Kadipiro urban village. The type of this research was descriptive quantitative and the research method which was used was survey. The population in this research was as many as 14,818 heads of family affected by flood disaster in Kadipiro Urban Village, Banjarsari Sub-district, Surakarta city, based on the monographic data of village 2015. The samples of this research were taken randomly as many as 99 heads of family. The variable of research included the independent variable that was the readiness of the society and the dependent variable which was the action of the society in reducing the risk of flood disaster. The techniques of data collection which were used were the methods of questionnaire, interview, observation and documentation. The techniques of analysis used in this research were the experiment of questionnaire, the validity test, and the reability test. The result of this research revealed that the index of the threat level of flood disaster in Kadipiro Urban Village, Banjarsari Sub-dustrict was categorized as medium. The level of loss in the loss index in Kadipiro Urban Village was categorized as high class. The level of risk of flood disaster in Kadipiro Urban Village was categorized as medium. The level of readiness of the society in Kadipiro Urban Village, Banjarsari Sub-district on the flood disaster obtained a final score as much as 82.95 which was in the interval 80-100. From the above results, it could be categorized that the readiness of the society on the flood disaster in Kadipiro Urban Village, Banjarsari Sub-district was very ready.